Review paperPotential role of ultrasound imaging in interstitial image based cervical cancer brachytherapy - Kamrava, Mitchell (Journal of Contemporary Brachytherapy, 2014)
In 2012, more than 500,000 cases of cervical cancer were diagnosed worldwide. Over three quarters of these cases occur in less developed countries [1]. Advancements in image-guided brachytherapy are resulting in improved outcomes and reduced morbidity for women with this disease, but its worldwide adoption is hampered by lack of accessibility to advanced imaging techniques. Ultrasound is emerging as a potential option for tumor visualization, brachytherapy catheter placement, and treatment planning. While additional work is needed, ultrasound can potentially serve as the sole imaging modality for catheter insertion and planning. This paper will review our current knowledge on the use of ultrasound in interstitial brachytherapy treatment for cervical cancer.